Exchange market algorithm for economic load dispatch. (February 2016) - Ghorbani, Naser; Babaei, Ebrahim
Highlights: This paper presents EMA for solving economic load dispatch problems. EMA can be used as a reliable tool for solving practical ELD problems. The results of proposed algorithm are compared with other optimization algorithms. The results prove the robustness and effectiveness of the proposed algorithm. Abstract: This paper presents exchange market algorithm for solving economic load dispatch problems. Exchange market algorithm (EMA) is a new, robust, and strong algorithm to extract the optimal point for global optimization. Inspired by the stock exchange trading method, EMA strives to solve optimization problem. Meticulous investigation of the stock exchange methods employed by the elites in such markets has yielded to shape this algorithm. This algorithm has two searcher operators as well as two absorbent operators for individuals to be absorbed to the elite person, which leads to creation and organization of random numbers in the best way. In order to show the abilities of the EMA, this algorithm has been implemented on four test systems in different dimensions (3, 6, 15 and 40 units) with convex and nonconvex cost functions. The numerical results have been compared with the results of some new and strong algorithms. The results prove the robustness and effectiveness of the proposed algorithm and show that it could be used as a reliable tool for solving practical ELD problems.